Essential gear for mobile recording - Rizzo, Carmen; Safari eBooks ([S.l.] : Total Training, 2009)
"No longer is your musical creativity confined to the walls of a recording studio. Today with a little planning and the right gear, you can record audio whenever and wherever you want. Two-time Grammy nominated recording artist and musician Carmen Rizzo shows you all the audio gear necessary for on-location recording. PLUS, Carmen shows you that it can all fit into two carry-on bags you can stow into the overhead compartment of most major airliners. Learn valuable tips from a seasoned pro about the best way to travel light without sacrificing any of your audio recording quality"--Resource description page.
Title from resource description page (viewed Oct. 5, 2009).
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Electronic reproduction.
Keywords: Sound -- Recording and reproducing -- Equipment and supplies; Electronic books